Pengaruh Kepemimpinan Transformasional, Lingkungan Kerja Terhadap Kinerja Karyawan di Era Digital - Nuraini Rasyid; Nurhani; Arsyad Paweroi (CV. Creative Tugu Pena, 2024)
Performance appraisal is an important aspect in assessing employee performance achievement. The main objective of this study is to determine whether Transformational Leadership, Work Environment has an effect on Employee Performance in the Digital Era. This study uses a quantitative method with a survey design to test the effect of transformational leadership and performance environment on employee performance. Primary data were collected through questionnaires distributed to 31 respondents selected by purposive sampling, with the criteria of employees who have worked at least one year in the company. The questionnaire consists of demographic questions, questions about transformational leadership, performance environment, and employee performance, with a 5-point Likert scale to measure respondent responses. The data obtained were then analyzed using SmartPLS software. The analysis stages include testing the measurement model (outer model) to ensure the validity and reliability of the instrument by testing the Average Variance Extracted (AVE), Composite Reliability (CR), and Cronbach's Alpha. Furthermore, testing the structural model (inner model) is carried out to test the research hypothesis by looking at the path coefficient value and significance level (p-value). Transformational leadership has a positive and significant effect on Employee Performance with an original sample value of 0.641, a T-statistic value of 3.782 and a p-value of 0.000. With this leadership style focusing on inspiration and motivation, which is able to encourage employees to achieve their maximum potential Performance environment does not affect employee performance with an original sample value of 0.299, and a p-value of 0.069. These results indicate that the p-value of 0.069 is greater than 0.05. This means that a conducive work environment is often considered important to support employee productivity and well-being, research shows that this factor does not always play a major role in determining individual performance.